Analisis Kesalahan Penggunaan Bahasa Indonesia dalam Laras Hukum pada Direktori Putusan Mahkamah Agung Republik Indonesia - Asista, Aruna; Suntara, Reza Adriantika (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study aims to describe the variations of errors that arise in the use of Indonesian with elements of legal language contained in the Directory of Decisions of the Supreme Court of the Republic of Indonesia in the Decisions of the Supreme Court of the Republic of Indonesia.This research is a qualitative descriptive research that is documentative or library research. Data collection is carried out through documentation techniques by examining several references to the use of legal language, both in the form of books, journals, magazines, newspapers, research reports, and legal documents relevant to the problem under study. The author records all matters related to the phenomenon of using legal language obtained from the Decision of the Supreme Court of the Republic of Indonesia as well as relevant documents, into a prepared notebook (Korpus). The data in this study is the use of legal language in the Directory of Decisions of the Supreme Court of the Republic of Indonesia with the determination of decision number 111/Pdt.P/2022/PN Pgp. The results of the analysis show that there are still many deep language errors in legal decisions seen from phonology, morphology, semantics, and syntax.